1971
DOI: 10.1063/1.1676654
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Vaporization and Thermodynamics of the Titanium Oxides. VII. Mass Spectrometry and Dissociation Energies of TiO(g) and TiO2(g)

Abstract: Two experiments of the successive vaporization type, five mass spectrometric vaporization experiments, and two isomolecular exchange reaction experiments were undertaken to resolve discrepancies in the thermodynamics of the titanium—oxygen system. The first two types of experiments confirmed that Ti3O5(s) is the congruently vaporizing phase. The second type of experiment showed that the principal reaction accounting for the congruent vaporization is Ti3O5(S)=TiO(g)+2TiO2(g). In the third type of experiment, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…They also have studied isomolecular reactions in order to determine DoO[TiO(g)]. They principally used Reaction (3) and confirmed the previous results of Drowart et al 6 From the studies of Drowart et al 6 and of Hampson and Gilles 7 …”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…They also have studied isomolecular reactions in order to determine DoO[TiO(g)]. They principally used Reaction (3) and confirmed the previous results of Drowart et al 6 From the studies of Drowart et al 6 and of Hampson and Gilles 7 …”
Section: Introductionsupporting
confidence: 53%
“…Their vapor pressure measurements were interpreted using Reaction (2) 7 have performed extensive mass spectrometric studies. Through studies of several phases in this sytem they confirmed .the congruent vaporization of Th05(S, (3) from W effUSIon cells.…”
Section: Introductionmentioning
confidence: 99%
“…3 were fit by unweighted least squares to obtain E(obs, mV) ----(303.6 • 5.0) --(0.1382 ___ 0.0040)T(K) [7] while the data corrected for the solubility of oxygen in niobium via Eq. 3 were fit by unweighted least squares to obtain E(obs, mV) ----(303.6 • 5.0) --(0.1382 ___ 0.0040)T(K) [7] while the data corrected for the solubility of oxygen in niobium via Eq.…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain gaseous ternary titaniummolybdenumoxygen and titaniumtungstenoxygen species a mixture of titanium oxide Ti 3 O 5 and silicon dioxide was evaporated from molybdenum or tungsten effusion cells, respectively. Ti 3 O 5 was selected because it is known [26][27][28][29] that this oxide evaporates congruently. The SiO 2 oxide was taken as a source of oxygen, which oxidized the cell and produced gaseous XO 2 and XO 3 oxides.…”
Section: In Situ Synthesis Of Gaseous Titanium Molybdates and Tungstatesmentioning
confidence: 99%